Manajemen pendidikan Islam: Menghadapi globalisasi dengan prinsip-prinsip Islami - Afifuddin, Muhammad Abdillah (Maliki Interdisciplinary Journal, 2024)
This article reviews the challenges of globalization in the context of Islamic education and the urgency of Islamic education management in maintaining religious identity and values while adjusting to the dynamics of the times. A holistic approach that integrates Islamic principles in all stages of education management, such as planning, organizing, directing and controlling, is the key to creating an effective learning environment with religious character. By referring to Qur'anic verses, this article emphasizes the importance of leadership with integrity and responsibility in building institutions that are fair and oriented towards the common good. In addition, the principle of continuous supervision is explained as an important strategy to ensure consistency and achievement of the set educational goals.